Phubbing in Social Solidarity Study (Ethnographic Study Of Social Solidarity Tapping Repong Damar Krui, Pesisir Barat Regency, Lampung Province) - Ratna Puspitasari; Berlin Toni (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2021)
During the pandemic, smartphones have become an urgent need for young people who have changed offline channels to online. On the one hand, smartphones bring progress to people of all ages, but on the other hand, it creates a new habit, smartphone addiction, so that they often ignore the presence of other people around them, even their parents in front of them. This is a new form of social behavior. West Lampung has extraordinary natural potential. Damar is the identity of the Krui community. Spong's eye resin covers an area of ​​17,500 hectares with a total of 1,750,000 cat's eye resin trees with an average production of 315 tons per year which is exported to Italy, India, Bangladesh, Pakistan, and the United Arab Emirates with employment from a wide range of people including youth. The young people who tap the resin often seem busy with their gadgets in their hands, so they don't have any concern or care for anyone around them. Because it has become a common and symptomatic phenomenon. Pandemic is a condition that never ends and requires social solidarity. So a contradiction arises in the community of Krui resin tappers. This study uses an ethnographic study with the theory of social solidarity by Emile Durkheim and Anthony Giddens. The theoretical implication is that strengthening social solidarity is the other side of phubbing, and the practical implication is the ethnographic revitalization of youth in Krui.